Pengaruh Keputusan Pendanaan Dan Keputusan Investasi Terhadap Nilai Perusahaan Dengan Harga Saham Sebagai Variabel Intervening Pada Perusahaan Manufaktur Subsektor Makanan Dan Minuman Yang Terdaftar Di Bei Periode 2020-2024 - Nezy Nurhidayah; Elfiswandi .; Putri Intan Permata sari (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the influence of financing decisions, investment decisions, and firm value, with stock price as an intervening variable, on food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Purposive sampling was used to select companies that met the research criteria. Data analysis methods included descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, hypothesis testing, and path analysis. The results indicate that financing decisions and investment decisions significantly influence stock prices. Furthermore, financing decisions and stock prices also significantly influence firm value. However, investment decisions do not significantly influence firm value. Furthermore, the analysis shows that stock prices do not mediate the effect of financing decisions on firm value, nor do they mediate the effect of investment decisions on firm value. This indicates that financing decisions and investment decisions influence firm value more directly than through the stock price mechanism.